2007
DOI: 10.1186/bcr1664
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 therapy. HER-2/neu diagnostics in breast cancer

Abstract: HER-2/neu status of the primary breast cancer (PBC) is determined by immunohistochemistry and fluorescent in situ hybridization. Because of a variety of technical factors, however, the PBC may not accurately reflect the metastatic tumor in terms of HER-2/neu status. Recently published guidelines recommend that tumors be defined as HER-2/neu positive if 30% or more of the cells are 3+. Circulating levels of the HER-2 extracellular domain can be measured in serum using a test cleared by the US Food and Drug Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…We demonstrated that coexpression of these molecules was associated with worse prognosis than high HER2/neu alone, indicating that Grb7 coexpression might be necessary for HER2/neu function. The importance of HER2/neu in breast cancer is well established [41]; HER2/neu is overexpressed in approximately 20%-30% of invasive breast cancers and is original article Annals of Oncology associated with poor prognosis, as reviewed previously [42]. Drugs that target HER2/neu have been shown to prolong survival, as reviewed previously [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that coexpression of these molecules was associated with worse prognosis than high HER2/neu alone, indicating that Grb7 coexpression might be necessary for HER2/neu function. The importance of HER2/neu in breast cancer is well established [41]; HER2/neu is overexpressed in approximately 20%-30% of invasive breast cancers and is original article Annals of Oncology associated with poor prognosis, as reviewed previously [42]. Drugs that target HER2/neu have been shown to prolong survival, as reviewed previously [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The serum HER-2 test using the ADVIA Centaur assay is approved by the Food and Drug Administration (FDA) for follow-up and monitoring of patients with metastatic breast cancer (MBC) whose initial serum HER-2 concentration is above 15 ng/mL (4).…”
Section: Introductionmentioning
confidence: 99%
“…Measured levels of the sECD-HER 2/neu protein greater than 15 ng/ml were indicative of the potential presence and the associated progression of primary tumors to metastatic breast cancer [4,6,7]. Most commercially available assays use this concentration as a focal point leaving smaller amounts undetected.…”
Section: Introductionmentioning
confidence: 99%
“…The human epidermal growth factor HER-2 oncogene (cerbB-2) has been implicated in this disease [1][2][3][4]. The HER-2/neu oncoprotein is amplified and over-expressed in 25 to 30 percent of patients with aggressive breast cancer.…”
Section: Introductionmentioning
confidence: 99%